Analisis Kebutuhan dalam Redesign Identitas Visual PHD (Peternakan Hijau Daun) Nusantara Kabupaten Trenggalek - Ghani Rahman Hadiid; Pungky Febi Arifianto; Bayu Setiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the need for redesigning the visual identity of PHD (Peternakan Hijau Daun) Nusantara as an effort to strengthen the brand image as an arts and culture-based educational tourism destination. The problems underlying this research are the inconsistent visual identity, the lack of representation of the brand's character, and the low level of audience recognition of PHD Nusantara. The research methods used include observation, interviews, and questionnaires. The results of the analysis indicate several main factors that form the basis for the need for redesign, namely the inconsistency of visual elements, the weak strength and readability of the logo, the inconsistency of the visual identity with the character of the destination, and the suboptimal visual experience of the audience at various interaction points. Based on these findings, it can be concluded that the development of a more consistent, communicative, and characteristic visual identity is needed as a basis for the redesign process. The results of this study are expected to be a reference in redesigning a visual identity that can strengthen the image of PHD Nusantara and increase its appeal to the audience.